Case report: Complete pathologic response with first-line immunotherapy combination in a young adult with massive liver dissemination of mismatch repair–deficient metastatic colorectal cancer: Immunological and molecular profiling - Bergamo, Francesca; Dalla Santa, Silvia; Loupakis, Fotios; Cerma, Krisida; Tosi, Anna; De Grandis, Caterina; Dalla Pietà, Anna; Gringeri, Enrico; Angerilli, Valentina; Ramondo, Gaetano; Rago, Alessandro; Cecchi, Fabiola; et al. (Frontiers in Oncology, 2022)
The current level of evidence for immunotherapy in previously untreated microsatellite unstable metastatic colorectal cancer is based on recent evidences of few studies that demonstrated durable response and clinical benefit, in term of objective response rate, disease control rate and progression free survival in this subgroup of patients. Based on combinatorial immunotherapy with nivolumab plus ipilimumab, we report the exceptional case of a complete pathological response in a 21-year-old woman presenting a clinically aggressive stage IV colorectal cancer with massive nodal and liver involvement. Extensive molecular analyses based on whole genome next-generation DNA sequencing, RNA sequencing, fluorescent multiplex immunohistochemistry and flow cytometry, provided a detailed description of tumoral and immunological characteristics of this noteworthy clinical case.